Cadmium and morphological alterations in the rotifer Philodina cf. roseola (Bdelloidea: Philodinidae) and the worm Aeolosoma hemprichi (Annelida: Aeolosomatidae): Cadmium-induced morphological alterations - Pérez-Yañez, Daniela; Soriano-Martinez, Danika Ruth; Damian-Ku, Mendy Eded; Cejudo-Espinosa, Eduardo; Alvarado-Flores, Jesus (Revista de Biología Tropical, 2019)
Cadmium is a toxic metal for zooplankton that produces deformations. Therefore, we used two native zooplankton species from Quintana Roo, Mexico, to obtain data regarding cadmium toxicity including the threshold concentration for observable morphological alterations and the percentage of organisms with morphological alterations at the exposure concentrations. We used the rotifer Rotaria sp. and the oligochaeta Aeolosoma hemprichi, both fed with the alga Nannochloropsis oculata. Then, Rotaria sp. and A. hemprichi were exposed to a cadmium concentration range from 0.05 to 10.0 mg L-1. The LC50 for cadmium in Rotaria sp. was 0.7 mg L-1, whereas in A. hemprichi it was 3.38 mg L-1. Cadmium at 0.5 mg L-1 for ≤24 h induced morphological alterations in the lorica of rotifers, foot deformations, and constriction in the middle part of the body. In oligochaetes, damage to the epidermis was noted. The threshold concentration where deformations appeared in rotifer was 0.3 mg L-1 at 24 h and in oligochaeta was 0.5 mg L-1 at 30 min.